Examining Financial Literacy, Knowledge and Socialization in Student Financial Behaviour in Nepal - Paudel, Prabhat (Kalika Journal of Multidisciplinary Research, 2025)
In today’s multifaceted financial world, it is more important than ever to help students learn how to make smart financial decisions. University students, as future professionals, are at a critical stage where financial literacy, knowledge, and social influences shape lifelong financial behavior. This study aims to understand the extent to which financial literacy, knowledge, and socialization affect financial behavior among university students in the Rupandehi District of Nepal and also the relationship among these variables and assess their combined effect through regression analysis. Information was obtained from 450 university students using a well-designed structured questionnaire. Students’ attitudes toward financial behavior were measured using a five-point Likert scale, while other structured questions were used to assess their financial status and objective knowledge. The findings indicate that most of the students are financially literate and have sufficient knowledge for useful financial decisions. Furthermore, interactions with family, friends, and media play a key role in shaping students’ financial behavior. The regression analysis confirms that financial literacy, knowledge and socialization each have a statistically significant and positive impact on financial behavior. The evidence indicates the crucial role of enhancing financial education and leveraging social influences enhance students’ ability to make responsible financial choices.